Eksistensi Ajaran Tantrayana dalam Kehidupan Beragama Hindu di Bali - Ida Ayu Devi Arini; Ida Bagus Gede Paramita (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Tantrayana is a teaching found in the books of Tantra-Sastra which in the development of Shiva Siddhanta in Bali is mentioned based on: Catur Marga (Bhakti Marga Yoga which pays main respect to Karma Marga yoga and Jnana Marga Yoga). Tantrayana emphasized the importance of religious ceremonies (rituals), because the role of religious ceremonies is an activity to create a balance of life in this world. In the Mahanirwana Tantra book, the principles of the Panca Yadnya ceremony are laid out that need to be carried out. It also mentions the means related to caru, such as animal sacrifice. The Tantrayana describes in detail the procedures for performing the yadnya and to whom it is offered. By paying attention to the contents of the Tantra Sastra books containing Tantrayana teachings, it can be understood that the forms of ceremonies and yajna ceremonies that are held in Bali, it is clear that there is an influence from Tantrayana.The purpose of writing this article is to know in general the existence of Tantrayana understanding in religious life in Bali, especially among the younger generations.This research is a qualitative descriptive research with a functional approach. The data collection method in this article is literature study. The results of this study are the knowledge of the concept of Tantrayana teachings, how much this teaching is adopted by Hindu religious life, including the way of art and the lifestyle of the younger generation.